Winter School: Encounter with Ceramics - Rocha, Clara Pitanga; Bombardi, Alice Roger; Rodrigues, Brunno Figueiredo; Isidoro, Beatriz Araújo; Castelli, Henry Silva; Leonel, Priscila (Revista do Colóquio, 2024)
This experience report addresses the Laboratory of Artistic Experimentation in Ceramics, held from July 1 to 5, 2024 at the UNESP Institute of Arts, São Paulo campus. The event promoted integration between students from UNESP and ETEC Carlos de Campos, addressing ceramics and its ancestral and scientific dimensions. The event included practical and theoretical activities such as the construction of a traditional wood-fired oven and the modeling of ceramic pieces in conjunction with the research developed by the graduate students participating in this activity. The initiative also highlighted the importance of university extension and academic exchange.